Proximity and Horizontal Policies : The Backbone of Export Diversification - Salinas, Gonzalo (IMF Working Papers; Working Paper ;, 2021)
The lack of a clear link between general economic fundamentals and export diversification indicators in the literature has fueled the believe that industrial policies are an absolute requisite to diversify exports. This paper, however, does find a strong statistical connection between horizontal policies and diversification by making two novel changes to traditional methodologies: using export categories that lead to diversification (for example, manufactures) as dependent variables, and using a gravity-equation regression setting. Proximity to other economies explains about a third of cross-country heterogeneity in targeted exports, and four fifths together with horizontal policies. Australia, Chile, and New Zealand emerge as new role models for diversification policies.